Engineering Personnel Training System in Modern Russia: Educational Trajectories and Quality Control - A. N. Danilov; M. B. Gitman; V. Yu. Stolbov; E. K. Gitman (Высшее образование в России)
The paper focuses on the structure of the Russian engineering personnel training system. Multivariance of training in the condition of a choice of educational trajectory is shown. The authors dwell on the role of an independent evaluation of professional qualifications conducted within the framework of quality control of engineers’ qualification. For this purpose, Centers for Qualification Assessment are being created, which may play an important role in the Russian system of engineers’ qualification assessment. The requirements to these centers and possible evaluation procedures are described. The authors study the foreign experience of two-tier system for assessment quality of engineering personnel preparedness for professional work. The paper stresses the need to create modern funds for assessment the level of professional competencies agreed with employers in accordance with industry professional standards.The authors recommend applying the joint experience of universities and enterprises in working out fund of assessment tools comprising situational tasks for the procedure of final attestation of graduates